303 Integrated Care Hubs for the Older Person: RIGHT TIME, RIGHT PLACE. (16th September 2019) - O'Donoghue, Alice; MacMahon, Clare; Bolger, Margaret; Roche, Suzanne; Phelan, Niamh; Murphy, Catherine; Grant, Emma; O'Donnell, Desmond; O'Mahony, Anne; Henin, Maged; O'Gorman, Millie; Masombo, Rudo; et al.
Abstract: Background: Our Integrated Care Hub has been operating since mid-2017 providing patient-centred multidisciplinary team (MDT) care operating via a number of specialised care pathways. There has been an early emphasis on the response to crisis presentations and with the introduction of the Hub we now have an extensive and organised response to such presentations. We wanted to assess does this system result in earlier referral of the 'Crisis' patient to an Integrated Care Hub. Methods: We performed a retrospective quantitative analysis of data comparing two time-periods January to June 2018 with January to April 2019 (year-to-date). The number and type of MDT contacts were classified into 4 categories: Immediate Crisis (would present to the Emergency Department within 48 hrs if not reviewed), Emerging Crisis (would present to the Emergency Department within 2 weeks if not reviewed), Stable Situation (needs optimisation), Stable Situation (no intervention). Data were extracted from File-Maker Pro. Results: There were 424 MDT contacts in January-June 2018 compared with 658 MDT contacts in the year-to-date 2019. The number of patients in these time-periods presenting in 'Immediate Crisis' was reduced in the year-to-date 2019 - 4.41% when compared to the same time-period in 2018 – 11.79%. There was a similar reduction in 'Emerging' Crisis presentations in these time-periods: 15.65% in 2019 vs. 24.29% in 2018. While the patients attending that were classified as Stable Situation (needs optimisation) increased in 2019 compared to 2018 – 66.57% vs. 47.88%. Conclusion: We can see from our data that the creation of our Integrated Care Hub has resulted in an increased demand for our service, however, interestingly we have found that the crisis patient load has, in fact, decreased. This suggests that we are influencing referral patterns by both recognising and intervening at an earlier stage to manage, stabilise and reverse crisis in these patients in an organised manner within the MDT.